1971
DOI: 10.5962/bhl.title.45480
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphology and sediments of the inner continental shelf : Palm Beach to Cape Kennedy, Florida

Abstract: The Inner Continental Shelf off eastern Florida was surveyed by CERC to obtain information on bottom morphology and sediments, subbottom structure, and sand deposits suitable for restoration of nearby beaches. Primary survey data consists of seismic reflection profiles and sediment cores. This report covers that part of the survey area comprising the inner Shelf between Palm Beach and Cape Kennedy. Sediment on beaches adjacent to the study area consists of quartzose sand and shell fragments. Median size of mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…The red reflector was previously reported by Meisburger and Duane (1969) From near False Cape southward, a reflector judged to be continuous with the red reflector is directly underlain by unit F having seaward-dipping internal reflectors. Meisburger and Duane (1971) and Field and Duane (1974) The white reflector like the overlying primary reflectors slopes consistently eastward (Fig. 17).…”
Section: Flagler Beachmentioning
confidence: 83%
See 4 more Smart Citations
“…The red reflector was previously reported by Meisburger and Duane (1969) From near False Cape southward, a reflector judged to be continuous with the red reflector is directly underlain by unit F having seaward-dipping internal reflectors. Meisburger and Duane (1971) and Field and Duane (1974) The white reflector like the overlying primary reflectors slopes consistently eastward (Fig. 17).…”
Section: Flagler Beachmentioning
confidence: 83%
“…Calcareous ooids, characteristic grain-types off Cape Canaveral, are absent from cores collected in this study, although they have been reported in deeper deposits seaward of the survey area by Terlecky (1967). Other calcareous grains reported farther to tlie south by Meisburger and Duane (1971) bases. Type F is finer, often contains a significant quantity of silt, and is less well sorted than type A sand.…”
Section: V3mentioning
confidence: 92%
See 3 more Smart Citations